The development of visual aesthetic sensitivity in students in China - Zhang, Ju; Du, Xu; Zhang, XiaoWei; Bai, XueJun (Frontiers in Psychology, 2023)
To examine the development of visual aesthetic sensitivity in students in China, 2387 students from age 9 to age 22 (excluding ages 16-17) were tested by the Visual Aesthetic Sensitivity Test-Revised. The development of visual aesthetic sensitivity across ages and genders, and the effect of artistic training on students' visual aesthetic sensitivity were examined. The data of primary school and junior middle school students were collected by paper tests completed collectively in class, while the data of university students were collected by distributing and collecting online. Result suggests that students' visual aesthetic sensitivity is relatively stable from age 9 to age 12 and increases at age 13. The visual aesthetic sensitivity of girls is significantly better than that of boys at age 15, 19 and 20 years of age. This study also found that artistic training improves students' visual aesthetic sensitivity.